Epididymal epithelial degeneration and lipid metabolism impairment account for male infertility in occludin knockout mice - Liu, Bao Ying; Zhang, Bao Li; Gao, Da Yuan; Li, Qing; Xu, Xin Yu; Shum, Winnie (Frontiers in Endocrinology, 2022)
Occludin (OCLN) is a tight junction protein and Ocln deletion mutation causes male infertility in mice. However, the role of OCLN in male reproductive system remains unknown. In this study, we found defective proximal epididymis in Ocln-null mice with impaired sperm mobility and fertilisation. Integrative omics analysis revealed the downregulation of gene clusters enriched in acid secretion and fatty acid metabolism in the Ocln-null epididymis, especially the enzymes related to the unsaturated arachidonic acid pathway. The number of proton-pump V-ATPase-expression clear cells, a key player of luminal acidification in the epididymis, declined drastically from prepubertal age before sperm arrival but not in the early postnatal age. This was accompanied by programmed cell death of clear cells and increased pH in the epididymal fluid of OCLN-deficient mice. The lipidomics results showed significantly increased levels of specific DAGs conjugated to unsaturated fatty acids in the Ocln-mutant. Immunofluorescent labelling showed that the arachidonic acid converting enzyme PTGDS and phospholipase PLA2g12a were prominently altered in the principal cells and luminal contents of the Ocln-mutant epididymis. Whereas the carboxylate ester lipase CES1, originally enriched in the WT basal cells, was found upregulated in the Ocln-mutant principal cells. Overall, this study demonstrates that OCLN is essential for maintaining the survival of acid-secreting clear cells and unsaturated fatty acid catabolism in the mouse epididymis, as well as ensuring sperm maturation and male fertility.